CGIAR Research Program on Livestock - Plan of Work and Budget 2019 - CGIAR Research Program on Livestock (CGIAR Research Program on Livestock, 2019)
The Livestock CRP does not anticipate any major adjustments to its overall or Flagship Theories of Change in 2019. However, efforts continue to refine key product lines for each Flagship to ensure tighter alignment of the research agenda and activities to targeted intermediate development outcomes.